PEMURNIAN PARSIAL DAN KRISTALISASI PAPAIN DARI GETAH Carica papaya - Dwi Putri Mashfufatur Rohmah; Sofijan Hadi; Afaf Baktir (Jurnal Kimia Riset, 2019)
AbstractThis research has done partial purification by fractionation and optimization crystallization of papain from Carica papaya latex with the addition of ammonium sulphate. The enhancement of purification factor was determined by its specific activity. The fractionation results show that papain fraction of Carica papaya can be obtained by adding 40-80% saturated ammonium sulphate, with the highest specific activity, i.e. 2,0819 U/µg and the factor purification increase of 6,27 fold than papain extract. Meanwhile, the highest total activity, i.e. 10,7780 U of papain crystals can be obtained by presipitant agent addition of ammonium sulphate in the level / concentration 80% saturated at 15 °C. Microscopycally papain crystals profile in this condition have cube and tetragonal shape.Key words: crystallization, fractionation, ammonium sulphate, papain